An Unusual Case of a Tonsillolith - John Chan; Mamun Rashid; Yakubu Karagama (Case Reports in Medicine)
Tonsilloliths are rare calcified concretions that develop in tonsillar crypts within the substance of the tonsil or around it. Large tonsilloliths can mimic many conditions including abscesses or neoplasms. Given the wide range of differentials, it is difficult to diagnose tonsilloliths unless there is a considered emphasis on thorough history taking, careful inspection and a detailed characterisation of the lesion through digital palpation. This may be further supplemented with investigations such as plain radiography and computer tomography. Here, we illustrate a case with risk factors of oropharyngeal cancer and a history of fish bone impaction in the throat that was initially diagnosed as a “tonsillar foreign body” which turned out eventually to be a large tonsillolith.